2022
DOI: 10.1101/2022.06.14.496152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conservation at the uterine-placental interface

Abstract: The hemochorial placentation site is characterized by a dynamic interplay between trophoblast cells and maternal cells. These cells cooperate to establish an interface required for nutrient delivery to promote fetal growth. In the human, trophoblast cells penetrate deep into the uterus. This is not a consistent feature of hemochorial placentation and has hindered the establishment of suitable animal models. The rat represents an intriguing model for investigating hemochorial placentation with deep trophoblast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The uterine-placental interface from gd 18.5 was selected to obtain sufficient number of invasive trophoblast cells for analysis. Uniform manifold approximation and projection (UMAP) profiles of the uterine-placental interface were similar to previously published UMAP profiles for the rat uterine-placental interface (40). Cited2 expression was enriched in the invasive trophoblast cell cluster (Fig.…”
Section: Cited2 Deficiency and Invasive Trophoblast Cell Developmentsupporting
confidence: 83%
See 1 more Smart Citation
“…The uterine-placental interface from gd 18.5 was selected to obtain sufficient number of invasive trophoblast cells for analysis. Uniform manifold approximation and projection (UMAP) profiles of the uterine-placental interface were similar to previously published UMAP profiles for the rat uterine-placental interface (40). Cited2 expression was enriched in the invasive trophoblast cell cluster (Fig.…”
Section: Cited2 Deficiency and Invasive Trophoblast Cell Developmentsupporting
confidence: 83%
“…Uterine-placental interface tissues were dissected from gd 18.5 placentation sites (61), minced into small pieces, and enzymatically digested into a cell suspension for scRNA-seq as previously described (40, 63). Samples were then processed using Chromium Single Cell RNA-seq (10X Genomics) and libraries prepared using the Chromium Single Cell 3” kit (10x Genomics).…”
Section: Methodsmentioning
confidence: 99%
“…1B). At gd 19.5, 99.7 percent of invasive trophoblast cells located within the uterineplacental interface express Prl7b1 (Scott et al, 2022). snATAC-seq revealed that the regulatory region of Prl7b1 is accessible in the invasive trophoblast cell cluster (Fig.…”
Section: Prl7b1 Expression In the Rat Placentation Sitementioning
confidence: 97%
“…We recently performed single cell RNA-sequencing (scRNA-seq) and single nucleus assay for transposase-accessible chromatin using sequencing (snATAC-seq) for the rat uterine-placental interface from gestation day (gd) 15.5 and 19.5 (Scott et al, 2022;Vu et al, 2023). Prl7b1 was abundantly and specifically expressed within invasive trophoblast cells (Fig.…”
Section: Prl7b1 Expression In the Rat Placentation Sitementioning
confidence: 99%
See 1 more Smart Citation